PROSOCIAL ORGANIZATIONAL BEHAVIOR AND ITS DIFFERENT ASPECTS - R. H. ELKHDR, Hassan; KANBUR, Aysun (Atlas Journal, 2018)
In human relations helping behaviors of people have been trying to be understood. People also take the stage in organizations with their relations with others. Prosocial attitude is a multifaceted concept for organizations as in human life. Today, prosocial behavior is the topic of researches for psychologists, sociologists, managerial and organizational behavior scientists and professionals of human resources as well. It is generally believed that prosocial organizational behavior means “voluntary” acts that an employee does in the organization. However less is known about this kind of behavior, and therefore scientists have been trying to understand prosocial organizational behavior and even now, they have interest in knowing the still-unknown faces of this important subject. Even though many researches made significant contributions to the literature of prosocial organizational behavior in this respect, different aspects of prosocial organizational behavior needed to be analyzed. In this vein, the aim of this study is to explore prosocial organizational behavior and its aspects by understanding the concept with a literature review. In this context, types of prosocial organizational behaviors exhibited in organizations, different factors and reasons which trigger prosocial organizational behaviors, outcomes and benefits of prosocial organizational behaviors are explained in this study. Ultimately, it can be emphasized that prosocial organizational behaviors need to be encouraged due to their remarkable value for organizations